EDUCATIONAL MOTIVATION OF UNDERGRADUATE STUDENTS AS AN INDICATOR OF THE QUALITY OF EDUCATION - V. G. Antonov; T. Yu. Krotenko; M. B. Zhernakova; I. A. Rumyantseva (Вестник университета)
The motivation as one of the key indicators of the quality of higher education, as a powerful driver of the educational process, and one of the main catalysts of personal and professional growth of the student has been considered. The results of the diagnosis of the level of motivation and structure of the motivational complex, carried out with the help of two psychological techniques, modified by the authors of the article, have been briefly outlined and displayed. Possible reasons for the “lack” of motivation among students of management specialties have been identified. Meanwhile, it has been offered to look on the lack of motivation a little wider, than the authors were able to identify in the analysis of sources on this theme. Possible directions of optimization of motivational structure of future managers have been studied. The vector of further studies of educational motivation as an indicator of the quality of management education has been outlined.